Comparing the Effects of Short-Term Liuzijue Exercise and Core Stability Training on Balance Function in Patients Recovering From Stroke: A Pilot Randomized Controlled Trial - Zhang, Ying; Wang, Chen; Yang, JianZhong; Qiao, Lei; Xu, Ying; Yu, Long; Wang, Jie; Ni, Weidong; Wang, Yan; Yao, Yue; Yong, ZhiJie; Ding, ShanShan (Frontiers in Neurology, 2022)
Aims: Liuzijue Qigong (LQG) exercise is a traditional Chinese exercise method in which breathing and pronunciation are combined with movement guidance. Breathing is closely related to balance, and LQG, as a special breathing exercise, can be applied to balance dysfunction after stroke. The purpose of this study was to observe the clinical effects of short-term LQG exercise on balance function in patients recovering from stroke. Methods: Stroke patients were randomly divided into an Intervention Group (IG) (n = 80) and a Control Group (CG) (n = 80). The IG received conventional rehabilitation training plus LQG and the CG received conventional rehabilitation training plus Core Stability Training (CST). All patients received treatment once a day, 5 times a week for 2 weeks. The primary outcome was BBS. Secondary outcome measures were static standing and sitting balance with eyes open and closed, Fugl-Meyer Assessment (FMA), Maximum Phonation Time (MPT), Modified Barthel Index (MBI) and diaphragm thickness and mobility during quiet breath and deep breath. Results: Compared with the CG, the IG showed significant improvement in the BBS (11 (8–13) vs 9 (4–14), P = 0.039), MPT (2.30 (1.52–2.97) vs 1.51 (1.02-2.19), P = 0.001), MBI (10 (10–15) vs 5 (5–10), P = 0.001), diaphragmatic mobility during QB (0.48 (0.14–0.93) vs 0.24 (0.16-0.47), P = 0.01) and diaphragmatic mobility during DB (0.76 (0.28–1.49) vs 0.46 (0.21-0.67), P = 0.003), Cop trajectory in the standing position with eyes open (-100 (-143, -65) vs -86 (-118, -16), P = 0.034) and Cop area in the standing positions with eyes open (-100 (-150, -35) vs -43 (-129, - 4), P = 0.015), Cop trajectory in the seating position with eyes open (-23 (-36, –7) vs -11 (-20, -2.3), P = 0.001) and Cop area in the seating position with eyes open (-16 (-22, -9) vs -10 (-17, -6), P = 0.002). Conclusions: The short-term LQG combined with conventional rehabilitation training significantly improved the balance functions of stroke patients. It also improved static standing and sitting balance with the eyes open, diaphragm functions, maximum phonation time and the quality of daily life for stroke patients.